L’effet syrien et l’analyse géopolitique et géostratégique du Moyen Orient actuel. - Ioannis Mazis (Civitas Gentium, 2012)
This paper presents a systemic geopolitical and geostrategic analysis of the current enlarged region of the Middle East with respect to the Syrian effect, developing on the basis of the action of the Islamist movement and the re-distribution of power which it entails.